PREVALENCE OF BURNOUT SYNDROME IN HEALTH PROFESSIONALS DURING THE COVID-19 PANDEMIC - Buffon, Viviane Aline (2023)
Introduction: Burnout syndrome in the professional context is a condition caused by long-term stress in the workplace. In the face of the COVID-19 pandemic it has been observed that healthcare workers have experienced psychological health issues. Objective: This study aims to analyze different professional categories and sectors, identifying the main risk factors and coping mechanisms adopted by healthcare professionals associated with Burnout syndrome. Method: A literature search was conducted, and an electronic form was administered to healthcare professionals who provided direct medical care to COVID-19 diagnosed and hospitalized patients in the city of Curitiba, Brazil, from March 2020 to November 2021. The questionnaire included personal and professional information, as well as specific conditions experienced during the pandemic, coping strategies, and the application of the Maslach Burnout Inventory - Human Services Survey (MBI-HSS) to assess the prevalence of Burnout syndrome. Results: The sample consisted of 89 healthcare professionals, and a prevalence of 48.31% for Burnout syndrome was identified. No statistically significant results were found when analyzing different professional categories and sectors. However, changing sectors during the pandemic was statistically significant (p=0.0245), as well as seeking emotional/psychiatric/psychological support (p=0.0004), and the importance of using mediation during the pandemic (p=0.0027). Conclusions: Changing sectors during the pandemic was identified as the only risk factor in this study. The main coping mechanisms adopted by healthcare professionals during the COVID-19 pandemic to address Burnout syndrome included seeking emotional, psychological, and psychiatric support, as well as an increased use of psychotropic medication.